DETERMINING THE COMBINATION OF QUANTITY AND CAPACITY OF GAS COMPRESSORS FOR INCREASING GAS PRODUCTION AT THE GATHERING STATION OF PT PERTAMINA EP - Tambunan, Renold
In the oil and gas production process, one of the oil and gas lifting techniques is using the gas lift method. With this gas lift method, a natural gas compression system is needed to send gas back into the bowels of the earth. It is often found that the selection of compression equipment provided does not consider many aspects and only considers the cost aspect. This study aims to plan a decision-making model in determining the configuration or combination of how many compressors and compressor flow capacities are with several criteria, namely cost, Operational and Maintenance, the situation of existing facilities, and considering how much gas capacity can be flowed as well as alternative capacity configurations. used are 1 x 100% Capacity, 2 x 50% Capacity and 5 x 20% Capacity. With these several criteria, the method used is the Analytical Hierarchy Process (AHP). This method can facilitate input in the form of quantitative and qualitative. All the results of the discussion and the questionnaire were entered into the formula so that the normalized scores were obtained. The calculation is done online which was developed by Klaus D Goepel (2018) in processing data, so that the configuration for the compressor is obtained. For the capacity configuration according to the calculation results, priority is 2x50% Capacity where the alternative has the highest weight value in 6 of the 9 sub-criteria.